Fanzines - Triggs, Teal (London : Thames & Hudson, 2010)
This is the ultimate book on fanzines, amateur magazines produced by fans, for fans of a certain subculture. This illustrated book is full of reproductions of the best fanzines ever created, from the superhero tributes of the 1950s and 60s, to punk fanzines such as 'Sniffin Glue', right up the contemporary e-zine scene.
boek